Restructuring Process Analysis of the Organization of Regional Devices in Dharmasraya District - Muallimin, Elza Zikra; Pribadi, Ulung; Akta Padma Eldo, Dwian Hartomi (Universitas Muhammadiyah Yogyakarta, 2019)
Government Regulation No. 18 of 2016 has explained that the organizational restructuring process of regional apparatus is a process that has gone through the stages and roles that apply. Then, regional readiness in conducting institutional arrangements, so that the downsizing and fattening of the organization has an impact on the renewal of the organizational structure and renewal of field affairs which ultimately the organization can increase/decrease. The object of the research used was organizational restructuring in Dharmasraya Regency. This study uses the theory of Robbins (1994) which describes the related work, departmentalization, chain of command, range of control, centralization and decentralization and formalization. To find out the factors that influence organizational restructuring, researchers use indicators of formal rule approaches, performance evaluations, political processes, and human resources and apparatus. This study uses descriptive qualitative methods. Data collection techniques are carried out by direct interviews, indirect interviews and interpretation analysis of document documentation, reports, and other supporting documents. The results of this study are that the restructuring process of regional apparatus organizations in the Dharmasraya Regency is still largely supported by financial and budgetary factors, human resource factors or regional government apparatus, legislation factors, and political factors. In this study it can be concluded that the Dharmasraya District Government is still weak in the level of delegation of authority, the organization is still very poor in structure, and fattening is too large. Therefore, the factors that greatly influence the process of restructuring the regional apparatus organization in the Dharmasraya District Government are political interests and their implementation is political in nature.